NEEDS FOR EMPOWERING RURAL WOMEN IN VEGETABLE PRODUCTION IN THE TRANSITION TO SUSTAINABLE FAMILY FARMING SYSTEMS FROM THE PERSPECTIVE OF SPECIALISTS - AL-fatlawy, Rana S. AL-fatlawy; Lafta, Ahmed Hamdan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The current research aims to identify the needs required to enable rural women in the transition to sustainable family agricultural systems, as a questionnaire was prepared consisting of 5 axes of needs (institutional, guidance, economic, social and technological), which included 46 items, data was collected from  the research community represented by experts and specialists in the field of rural women's empowerment and sustainable agricultural development,  numbering 132 experts in Baghdad Governorate, and the research concluded that 91% of the paragraphs came at a level of great need and 9% of them came at  a  very  large level of need, and this is an indication that there is a large gap between the current situation of rural women and the situation required by the researchers recommended the need  to meet these needs through special programs for rural women involving all relevant authorities to achieve the transition to sustainable family agricultural systems.